Applications of catalytic C-N bond formation from diazo compounds - Douglas, Timothy (2019)
This thesis describes the development of a new reaction to form indolizines from pyridines, diazo compounds and alkynes, catalysed by commercially available iron catalysts. In addition, new methods for the in situ generation of diazo compounds via hydrazone oxidation have been developed. The introduction section introduces indolizidines and indolizines and the synthetic routes towards them, including the reaction of pyridinium ylides with alkenes and alkynes. Subsequently, methods for pyridinium ylide generation and synthesis of diazo compounds are discussed. Methods for the in situ generation of diazo compounds are described, specifically hydrazone oxidation. The final section details the use of laccase proteins in conjunction with mediators as oxidation catalysts. The results and discussions section is divided into three chapters. Chapter one describes the optimisation of catalytic indolizine synthesis, informed by observation of quinolizine and pyrazole by-products. Also discussed is a debromination reaction observed during the substrate scope variation. Chapter two discusses synthesis of diazo compounds via NCS mediated hydrazone oxidation, including the initial optimisation of this process, the synthesis of hydrazone substrates, and the testing of these substrates under the reaction conditions. Finally, the methodology was used to generate diazo compounds in situ and react them with anilines via NH insertion. Chapter three describes the biocatalyzed oxidation of hydrazones to diazo compounds and the successful of using this methodology to generate diazo compounds in situ and react them via NH insertion with aniline. Ultimately, NH insertion products were obtained without the need for controlled addition of reagents or pre-formation of the diazo compound. Finally, the experimental chapter describes the procedures by which the compounds in this thesis were synthesised, as well as full spectroscopic data and characterisation.